HUBUNGAN ANTARA RELIGIUSITAS DAN KESEJAHTERAAN PADA MASYARAKAT BANJAR, KALIMANTAN SELATAN - Sadewa, Manik Mutiara; Budiman, Mochammad Arif; Mairijani, Mairijani (Islamic Economics and Business Faculty of UIN Antasari, 2015)
Abstract: In Islam, there is a positive relationship and correlation between religiosity (religious) and welfare (Sura 7:96; 65: 2-4). However, different from the conventional concept which relates only to the dimensions of the material welfare alone, welfare in the concept of Islam has a wide spectrum and multidimensional. Unfortunately, so far not many empirical studies conducted to con? rm this relationship in the life of the Muslim community. This study was conducted using a survey on Muslim communities in South Kalimantan which is known as Islamic identity and a strong adherence to the teachings of Islam. Variables of religiosity and welfareare measured by a variety of dimensions and indicators which are developed from the concept of Maqasid al-Shariahand further processed by the method of principal component analysis (PCA) and con?rmatory factor analysis (CFA). Data analysis is using Structural Equation Modeling (SEM) showed religiosity in South Kalimantan Muslim community positively correlated with the level of welfare.